Dispersive waves and radiation trapping in optical fibers with a zero-nonlinearity wavelength - Hernandez, Santiago Martin; Sparapani, Alexis Cristian; Linale, Nicolás Martín; Bonetti, Juan Ignacio; Grosz, Diego Fernando; Fierens, Pablo Ignacio (Taylor & Francis Ltd, 2022)
Fil: Hernandez, Santiago Martin. Comisión Nacional de Energía Atómica. Gerencia del Área de Energía Nuclear. Instituto Balseiro; Argentina